The relationship between stigma and quality of life in hospitalized middle-aged and elderly patients with chronic diseases: the mediating role of depression and the moderating role of psychological resilience - Ji, Qiqi; Zhang, Lin; Xu, Jiashuang; Ji, Pengjuan; Song, Miaojing; Chen, Yian; Guo, Leilei (Frontiers in Psychiatry, 2024)
Objective Patients with chronic diseases may have some psychological problems due to their own or surrounding environmental factors, which can adversely affect the patient’s illness and life. Given that the number of chronically ill patients in China is currently increasing every year, more research is needed to determine the best ways to manage changes in psychological status and psychological stress responses in chronically ill patients. The researchers constructed a mediated moderation model to explore the impact of stigma on the quality of life of chronically ill patients, as well as the mediating role of depression and the moderating role of psychological resilience. Methods A stratified sampling method was used to select 363 middle-aged and old-aged patients with chronic diseases aged 45 years and older from the Affiliated Hospital of Zhejiang University for the study. Data were collected from patients with chronic diseases such as cardiac, respiratory, renal, and other chronic diseases using the Cumulative Illness Rating Scale for Geriatrics (CIRS-G), the Stigma Scale for Patients with Chronic Diseases (SSCI), the Patient Health Questionaire-9 (PHQ-9), the Quality of Life Inventory (SF-12), and the Conner-Davidson Resilience Scale (CD-RISC) were collected from patients with cardiac, respiratory, renal, and other chronic diseases. A descriptive analysis was used to describe the sample. Linear regression was used to evaluate the relationship between the variables. Mediation and moderation analyses were used to explore the mediating role of depression and the moderating role of psychological resilience. Results There was a moderate negative correlation between stigma and quality of life (r = -0.378, P < 0.01). There was a moderate negative correlation between depression and quality of life (r = -0.497, P < 0.01). There was a moderately positive correlation between psychological resilience and quality of life (r = 0.382, P < 0.01). There was a moderate negative correlation between psychological resilience and depression (r = -0.348, P < 0.01). There was a weak negative correlation between psychological resilience and stigma (r = -0.166, P < 0.01). There was a strong positive correlation between stigma and depression (r = 0.607, P < 0.01) The mediation study showed that stigma was a significant predictor of quality of life and that stigma and quality of life were mediated to some extent by depression, with the mediating effect accounting for 67.55% of the total effect. The direct path from stigma to depression is moderated by psychological resilience (β = -0.0018, P < 0.01). Conclusions Depression mediates the relationship between stigma and quality of life, while psychological elasticity plays a moderating role between stigma and depression, and when the level of psychological elasticity increases, the more significant the role of stigma on depression. As a physiologically and psychologically vulnerable group, patients with chronic diseases’ overall quality of life and mental health should be taken more seriously, and clinical workers should pay timely attention to the psychological and mental conditions of patients with chronic diseases and provide timely and appropriate interventions and therapeutic measures. The relevant results of this study also provide a new perspective for clinical work on psychological intervention for patients with chronic diseases.